Sequential MR Assessment of the Susceptibility Vessel Sign and Arterial Occlusion in Acute Stroke. Issue 3 (10th November 2015) - Ritzenthaler, Thomas; Lacalm, Audrey; Cho, Tae‐Hee; Maucort‐Boulch, Delphine; Klaerke Mikkelsen, Irene; Ribe, Lars; Østergaard, Leif; Hjort, Niels; Fiehler, Jens; Pedraza, Salvador; Louis Tisserand, Guy; Baron, Jean‐Claude; et al.
ABSTRACT: PURPOSE: Susceptibility vessel sign (SVS) may likely influence recanalization after thrombolysis. We assessed, through the European sequential MRI database "I‐KNOW, " the relationship between the presence of SVS on T2‐weighted gradient echo imaging, its angiographic counterpart on magnetic resonance angiography and its subsequent impact on recanalization after thrombolysis. MATERIALS AND METHODS: Initial clinical and MRI characteristics and early follow up were analyzed in acute ischemic stroke patients treated with rt‐Pa within 4.5 hours. Patients underwent multimodal MRI at admission. Sequential imaging performed 3 hours, 2 days and 1 month later allowed the analysis of SVS changes and recanalization. RESULTS: Fifty patients were included in the study. SVS was observed in 54% of cases at admission. SVS was still present in 46% patients at 3 hours, 16% at 2 days, and 0% at 1 month. It was an independent predictor of no recanalization after thrombolysis ( P = .04). After 3 hours, SVS disappeared in only 4 cases, and was not linked with recanalization on MRA. Conversely, when SVS persisted, a partial or complete recanalization was observed in 9 and 6 cases, respectively. CONCLUSIONS: SVS is a predictor of lower recanalization rate. Its disappearance is not necessarily correlated with recanalization.